Real-time Boredom Evaluation Technique in College Students - Leonardo Garro-Mena; Jenny Andrea Calderón-Castro (Revista Electrónica Educare)
Introduction. Various studies have associated boredom in educational processes with a variety of negative effects. It is believed that boredom is caused by a failure in the environment to fulfill our need for motivation. Many tools (scales) have been developed to measure it. However, these scales are designed to measure global boredom, that is, at the end of the process, not in its stages. The present study seeks to develop a methodology to evaluate the effect of boredom in the stages of a university class to have a tool for the quantitative evaluation of specific activities. Method. This study proposed a boredom measurement scale with a minimally disruptive intervention tool. The data obtained undergo mathematical processing to reduce the effect of subjectivity (perceived level of boredom) on the scale. The proposed methodology was applied to a group of students from the University of Costa Rica. Results. The most important result was the correlation between specific activities in a class and the gradient of boredom. Discussion. The reduction in the variability between students achieved with mathematical processing allows the proposed methodology to be used for the quantitative analysis of the stages of a class based on perceived boredom. This information can be used to design learning processes focused not only on the global process but on each stage of it, which, to the best of our knowledge, is not achieved by any of the commonly used scales.